1996
DOI: 10.1002/mawe.19960270510
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen der Schädigungsanisotropie auf die Lebensdauer von Stählen bei Zeitstandbeanspruchung

Abstract: The aim of the investigation is the prediction of the influence of creep history, e.g. pre-damage and pre-loading, on the further creep behaviour after changing the loading direction. The changing of the loading direction has a significant influence on the rupture-time. A model has been developed which describes the dependence of rupture-time from the anisotropic effect of damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Figure 12.5b shows the experimental data for the temperature 600 • C. Examples for minimum creep rate versus stress curves for various materials can be found in Boyle and Spence (1983);Illschner (1973); Kassner and Pérez-Prado (2004); Kraus (1980);Malinin (1981); Odqvist and Hult (1962);Odqvist (1974); Penny and Mariott (1995) and many papers related to the experimental analysis of creep, e.g. Altenbach et al (2013); Gariboldi and Casaro (2007);El-Magd et al (1996); Hyde et al (1997Hyde et al ( , 1999; Kimura et al (2009);Längler et al (2014). To discuss basic features of tertiary creep consider a sketch of the creep rate versus creep strain curves usually observed for 9-12 % Cr steels, Fig.…”
Section: Creep and Relaxationmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 12.5b shows the experimental data for the temperature 600 • C. Examples for minimum creep rate versus stress curves for various materials can be found in Boyle and Spence (1983);Illschner (1973); Kassner and Pérez-Prado (2004); Kraus (1980);Malinin (1981); Odqvist and Hult (1962);Odqvist (1974); Penny and Mariott (1995) and many papers related to the experimental analysis of creep, e.g. Altenbach et al (2013); Gariboldi and Casaro (2007);El-Magd et al (1996); Hyde et al (1997Hyde et al ( , 1999; Kimura et al (2009);Längler et al (2014). To discuss basic features of tertiary creep consider a sketch of the creep rate versus creep strain curves usually observed for 9-12 % Cr steels, Fig.…”
Section: Creep and Relaxationmentioning
confidence: 96%
“…For example one may interrupt the test after a certain creep exposure, cut specimen in different directions and perform subsequent creep tests to establish the effect of the induced anisotropy. Such tests are discussed in Betten et al (1995);El-Magd et al (1996). Another approach is to subject the specimen to the non-proportional loading with varying principal directions, or in other words to rotate the loading with respect to the material without interrupting the test.…”
Section: Multi-axial and Stress State Effectsmentioning
confidence: 99%
“…The preferential direction of micro-cracks depends on the material microstructure and on the kind of the applied stress. In [108] it is demonstrated that for small specimens pre-strained up to 0.25ε cr * the creep response is not sensitive to the angle θ. austenitic steel X8 CrNiMoNb 1616 and the ferritic steel 13 CrMo 4 4 is experimentally studied in [66,108] with respect to different loading orientations.…”
Section: Damage-induced Anisotropymentioning
confidence: 99%
“…The dependencies on stress and temperature are of primary interest to an engineer designing some structure or machine. [108,146,147,165]. From the resulting families of creep curves one can obtain the minimum creep rate vs. stress curve, the minimum creep rate vs. temperature curve, the creep rate vs. time curve and the stress vs. time to fracture curve (long term strength curve).…”
Section: Creep Phenomena In Structural Materialsmentioning
confidence: 99%
See 1 more Smart Citation